Developing mobile phone text messages for tobacco risk communication among college students: a mixed methods study. (December 2017) - Prokhorov, Alexander; Machado, Tamara; Calabro, Karen; Vanderwater, Elizabeth; Vidrine, Damon; Pasch, Keryn; Marani, Salma; Buchberg, Meredith; Wagh, Aditya; Russell, Sophia; Czerniak, Katarzyna; Botello, Gabrielle; et al.
Abstract Background Engaging young adults for the purpose of communicating health risks associated with nicotine and tobacco use can be challenging since they comprise a population heavily targeted with appealing marketing by the evolving tobacco industry. The Food and Drug Administration seeks novel ways to effectively communicate risks to warn about using these products. This paper describes the first step in developing a text messaging program delivered by smartphones that manipulate three messaging characteristics (i.e., depth, framing, and appeal). Methods Perceptions of community college students were described after previewing text messages designed to inform about risks of using conventional and new tobacco products. Thirty-one tobacco users and nonusers, aged 18–25 participated in five focus discussions held on two community college campuses. Attendees reviewed prototype messages and contributed feedback about text message structure and content. Qualitative data were coded and analyzed using NVivo Version 10. Results Most participants were female and two-thirds were ethnic minorities. A variety of conventional and new tobacco products in the past month were used by a third of participants. Three identified domains were derived from the qualitative data. These included perceived risks of using tobacco products, receptivity to message content, and logistical feedback regarding the future message campaign. Conclusion Overall, participants found the messages to be interesting and appropriate. A gap in awareness of the risks of using new tobacco products was revealed. Feedback on the prototype messages was incorporated into message revisions. These findings provided preliminary confirmation that the forthcoming messaging program will be appealing to young adults.